Estimation of heat dissipation on a levitating rotor over superconducting magnet bearing. Issue 1 (March 2020) - Iida, T; Sakurai, Y.; Matsumura, T; Sugai, H; Imada, H; Kataza, H; Ohsaki, H; Katayama, N; Terao, Y
Abstract: We report the estimation of the heat dissipation on a levitating rotor over superconducting magnetic bearing operating below 10 K. The continuously rotating mechanism is one of key devices to support the rotation of a sapphire half wave plate (HWP) in a polarization modulator of a LiteBIRD satellite. Due to the system requirement, the HWP must be kept at a cryogenic temperature while it is spinning. In order to minimize the frictional energy loss, we employ a superconducting magnetic bearing (SMB) and AC synchronous motor, which enables a contactless rotational mechanism. While we can minimize the frictional heat loss, there exists an energy loss due to the magnetic friction. As a result, it is essential to build a thermal model an estimation of heat dissipation to this contactless rotor is important to predict how much the HWP temperature rises during its rotation. For an estimation of heat dissipation, we conduct an experiment in order to establish the thermal simulation model equivalent to the flight model in size. Each thermal contact conductance between the rotor and the cryogenic rotor holder is also estimated through the experiment data. From the data, we only can know the difference in the rotor temperature before and after the rotor rotation. We monitor the transient temperature profile of grippers after the rotor is gripped by them. The rotational time is related to the total heat dissipation on the rotor because the heat dissipation is attributed to two kinds of energy losses: a magnetic hysteresis and induced eddy currents on metal parts of the rotor. Finally, we make a comparison between the thermal model and the experimental result and estimate the allowable heat dissipation to keep the HWP temperature lower than 20K.